Pembelajaran Daring Bahasa Indonesia di SMP Se-Kecamatan Kampar Kiri - Titik Winarsih; Muhammad Mukhlis (UIR Press, 2022)
This study examines the implementation of the Indonesian online learning process. This study aims to determine the implementation of the Indonesian language online learning process in junior high schools throughout the Kampar Kiri sub-district for the 2020/2021 academic year. The theory used to analyze the research problem uses the theory of Bilfaqih and Qomaruddin (2015). This type of research is qualitative research with phenomenological methods. The informants of this study consisted of 5 informants who came from SMPN 1 Kampar Kiri 2 teachers, SMPN 2 Kampar Kiri 1 teacher and SMPN 1 Atap Muara Selaya there were 2 teachers. Data collection techniques using interviews. Data analysis used the Stevick-Colaizzi-Kean phenomenological study technique. The result of this research is that the implementation of the Indonesian language online learning process in junior high schools throughout the Kampar Kiri District for the 2020/2021 Academic Year shows that the implementation has been maximized. This is evident from the results of the answers to several questions posed to the teacher indicating that Indonesian language teachers have implemented and implemented several procedures in the implementation of online learning, starting with providing material information, conducting exploration, elaborating in the implementation of learning, providing video explanations of the material, providing assignments or assessments directly online as well as providing a forum for uploading assignments and information in the form of WhatsApp groups for student study groups